Relação entre composição corporal e o estado nutricional de longevos - Safian, Claudia Aline Oliveira (2018)
Introduction: Brazil has undergone considerable changes in the age distribution of its population, with the elderly being responsible for almost 26 million inhabitants. Allied to this reality, is a series of nutritional disorders in this population segment. An important factor related to quality of life and healthy aging is good nutrition throughout life. Objective: To observe the possible relationship between the nutritional status and the body composition of the longevity. Methodology: This is a descriptive, cross-sectional and analytical study, with elderly individuals aged 90 years or older. The instruments used were the Mini Nutritional Assessment to evaluate nutritional status, Anthropometry to evaluate weight, height and BMI, and bioimpedance to evaluate body composition. Results: The sample consisted of 72 elderly individuals, with a mean age of 93.7 years, most female(72%), white (82%) and widowed (64%). Of the total longevity, 19.4% were classified with nutritional risk based on the Mini Nutritional Assessment. All anthropometric parameters presented lower averages among participants with nutritional risk. Regarding the bioimpedance parameters, in general the risk-free individuals presented higher averages of weight, maximum ideal weight, minimum ideal weight, BMI, lean mass, fat mass, percentage of fat mass and minimum percentage of fat mass. Conclusions: It was observed that most of the longevity were classified without nutritional risk based on MAN. The importance of not only nutritional assessment and diet quality in the multiprofessional care of the longevity, but also the presence of a nutritionist was clear, since the measurement of the nutritional risk in the third age requires the joint analysis of the several existing methods for the nutritional evaluation, in order to obtain global diagnosis and accurate analysis of the nutritional status of the longevity.